Adv. J. Grad. Res. 2017
DOI: 10.21467/ajgr.2.1.12-24
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis on Nutritional Status and its Associated Factors of Under Five Years Children in Nepal

Abstract: A B S T R A C TMalnutrition among under five year of age group is a major underlying cause of the child morbidity and mortality in many developing countries like Nepal. Nutritional status of children is a proxy indicator for assessing the health status of entire population. This study was carried out to evaluate the nutritional status of the most vulnerable age group of children (0-59 months) and to identify different factors associated with it. Generally three anthropometric indicators were often used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
3
3
2
Order By: Relevance
“…Similarly female were 0.82 times less likely to be stunted in another study conducted in Ethiopia by using 2016 Ethiopia demographic and health survey [ 72 ]. Residential status in this study was significantly associated with stunting which is in concordance with several other studies [ 51 , 63 , 64 , 71 , 73 ]. In the present study stunting was less prevalent in the children who were living in joint and extended family, however in contrast to this study another study conducted in urban slums of Maharastra India [ 54 ] found less prevalent of stunting among children living in nuclear family.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly female were 0.82 times less likely to be stunted in another study conducted in Ethiopia by using 2016 Ethiopia demographic and health survey [ 72 ]. Residential status in this study was significantly associated with stunting which is in concordance with several other studies [ 51 , 63 , 64 , 71 , 73 ]. In the present study stunting was less prevalent in the children who were living in joint and extended family, however in contrast to this study another study conducted in urban slums of Maharastra India [ 54 ] found less prevalent of stunting among children living in nuclear family.…”
Section: Discussionsupporting
confidence: 93%
“…Nearly two third of the children in this study were stunted which is in line with another study conducted in Rupandehi [ 40 ] and Kapilvastu district of Nepal [ 47 ]. However, in contrast to this study other studies such as study conducted in severely food-insecure households in Nepal [ 46 ], rural and urban Nepal [ 28 , 48 51 ], tribal population in Assam India [ 53 ], urban slums and rural area of Maharashtra, India [ 54 ], semi-pastoral communities of Tanzania, eastern Ethiopia [ 55 ] found lower proportion of under five children were stunted [ 7 ]. However, higher proportion of underweight was also found in some studies, such as study conducted at a Teaching Hospital in Bobo-Dioulasso, Burkina Faso found more than three fourth of HIV infected under five years children were stunted [ 56 ].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In terms of arable land per person, it crosses 181 persons per square kilometre [2]. The rapid population growth has an adverse effect on overall socioeconomic development as well as malnutrition in children [3]. The high and constant level population growth rate is considered as the main obstacle to sustainable development of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Wealth quintile and mothers education (MOH, 2017), size of the family (Pokhrel, Parajuli & Acharya, 2018), wealth index, size of the child at birth, ANC checkups, education, and sex of a child (Upadhyay & Bhusal, 2017) were significant variables for determining the Nutritional status of Children under 5 years. In this study, external family income (wealth index related factor), gender, number of children below 14 years at home and mother's literacy are significant for nutritional status of children in Chepang community, this leads that the determining factors for nutritional status under five years of age are similar in Chepang community and in other communities' children of Nepal.…”
Section: Discussionmentioning
confidence: 99%